No longer euroskeptics: the evolution of the strategy of «Brothers of Italy» - Maria O. Shibkova; Alena I. Nebyanskaya (Научно-аналитический вестник Института Европы РАН)
In the European Parliament elections, the incumbent Italian Prime Minister and leader of the political party «Brothers of Italy», Giorgia Meloni, was personally leading her party’s list in all constituencies and urged citizens to vote for her if they approve of her cabinet’s policies. However, being a vivid example of a populist and personalized party, «Brothers of Italy» in this election campaign bet not only on the image of Meloni herself, but also on a new strategy of building relations with the European Union. The aim of this article is a comparative analysis of the election programs of the ruling Italian party «Brothers of Italy» for national and European elections held over the last five years. Identifying and comparing the key priorities around which these program documents were built allowed us to trace the influence of the leftist agenda on the political course of «Brothers of Italy», which is considered center-right, as well as the evolution of the party’s strategy towards the European Union – from a Eurosceptic to a Eurorealist paradigm. With the ambitious goal of repeating the success of 2022 now at the supranational level, «Brothers of Italy» aim to create a broad center-right majority in the European Parliament and send the left into opposition, but this raises the question of how far the ruling Italian coalition will be able to maintain its unity depending on the outcome of the European elections.